2015
DOI: 10.1186/s12868-015-0182-2
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral hemorrhage outcomes following selective blockade or stimulation of the PGE2 EP1 receptor

Abstract: BackgroundInflammation following intracerebral hemorrhage (ICH) significantly contributes to secondary brain damage and poor outcomes. Prostaglandin E2 (PGE2) is known to modulate neuroinflammatory responses and is upregulated in response to brain injury as a result of changes in inducible cyclooxygenase 2 (COX-2) and the membrane-bound type of PGE synthase. Inhibition of COX-2 activity has been reported to attenuate ICH-induced brain injury; however, the clinical utility of such drugs is limited due to the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…However, without following this work with further experiments that utilize a FP receptor selective antagonist and agonist, caution should be used when interpreting the potential for the FP receptor as a therapeutic target for the treatment of ICH. Our findings are similar to those found with EP1 −/− mice post-ICH, and recently our group has shown that following activation of the EP1 receptor, astrogliosis, neutrophil infiltration, blood-brain barrie breakdown, and functional recovery all improved (Leclerc et al, 2015a ). Based on these findings, we hypothesize that the activation of the FP receptor will result in measurable changes in the improvement of functional and anatomical outcomes following ICH.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, without following this work with further experiments that utilize a FP receptor selective antagonist and agonist, caution should be used when interpreting the potential for the FP receptor as a therapeutic target for the treatment of ICH. Our findings are similar to those found with EP1 −/− mice post-ICH, and recently our group has shown that following activation of the EP1 receptor, astrogliosis, neutrophil infiltration, blood-brain barrie breakdown, and functional recovery all improved (Leclerc et al, 2015a ). Based on these findings, we hypothesize that the activation of the FP receptor will result in measurable changes in the improvement of functional and anatomical outcomes following ICH.…”
Section: Discussionsupporting
confidence: 92%
“…This may explain why our findings with the FP −/− mice are consistent with our previous findings with the EP1 −/− mice using the same ICH model; the EP1 −/− mice showed greater deteriorated outcomes compared to WT control mice (Singh et al, 2013 ). Our groups also found recently that use of EP1 receptor agonists improved anatomical outcomes and functional recovery (Leclerc et al, 2015a ). In contrast to ICH, the genetic deletion and/or pharmacological blockade of either the EP1 or FP receptor types attenuated brain injury and improved neurological outcomes in excitotoxicity and mouse ischemic stroke models (Ahmad et al, 2006 , 2008 ; Saleem et al, 2007 , 2009 ).…”
Section: Discussionsupporting
confidence: 67%
“…The inducible isoforms of these enzymes, COX-2 and mPGES-1, are increased after brain injury and have been reported to have damaging effects in stroke models (11,20). PGE 2 exerts a broad range of physiologic and pathologic effects that can be both neuroprotective and neurotoxic through its ability to bind mainly to four different EP receptors, EP1-4, which are a family of G protein-coupled receptors with different downstream signaling pathways (1,2,19,20,24). In this study, we focus on the role of the EP3 receptor, the most abundant EP receptor in the body, including the brain (20,36).…”
mentioning
confidence: 99%
“…The NDS was assessed at 24, 48, and 72 h post-MCAO surgery in a double-blind fashion by two investigators. We followed a 24-point neurological scoring system, as we described previously [29,30]. In brief, the test includes six parameters: body symmetry, gait, climbing, circling behavior, front-limb symmetry, and compulsory circling.…”
Section: Neurological Deficit Score (Nds)mentioning
confidence: 99%